Kesulitan Orang Tua dalam Identifikasi Awal Gejala Stunting: Parental Difficulties in Early Identification of Stunting Symptoms - Halimatussa'diah; Ade Yayang Hernida; Annisa Dwika Putri Sitompul; Dea ningsih (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
This study investigated the factors that make it difficult for parents to identify early symptoms of stunting in children aged 0-2 years. Findings showed significant associations between maternal occupation, immunisation and income and stunting status among under-fives, while access to health services and attitudes towards child health behaviours also played an important role. A systematic review of nutrition interventions confirmed the effectiveness of such programmes with an emphasis on cultural appropriateness. The identification of predisposing factors for stunting, such as gender, LBW and exclusive breastfeeding, provides useful insights for designing more specific interventions. The study also underscores the role of poor parenting in the incidence of stunting in early childhood, where factors such as education, knowledge, income, family size and parenting within the family play a central role. The conclusions of this study provide a strong basis for the development of more focused stunting prevention programmes, demonstrating the need for improved accessibility of health facilities, attention to policies supporting the health of working mothers, and a holistic approach to improving positive parenting.   ABSTRAK Penelitian ini menyelidiki faktor-faktor yang menyulitkan orang tua dalam mengidentifikasi awal gejala stunting pada anak usia 0-2 tahun. Temuan menunjukkan adanya keterkaitan yang signifikan antara pekerjaan ibu, imunisasi, dan pendapatan dengan status stunting pada balita, sementara akses terhadap layanan kesehatan dan sikap terhadap perilaku kesehatan anak juga memiliki peran penting. Tinjauan sistematis terhadap intervensi gizi mengonfirmasi efektivitas program-program tersebut dengan penekanan pada penyesuaian budaya setempat. Identifikasi faktor predisposisi stunting, seperti jenis kelamin, BBLR, dan pemberian ASI eksklusif, memberikan wawasan yang berguna untuk merancang intervensi yang lebih spesifik. Penelitian juga menggarisbawahi peran pola asuh yang buruk dalam kejadian stunting pada anak usia dini, di mana faktor-faktor seperti pendidikan, pengetahuan, pendapatan, jumlah anggota keluarga, dan pola asuh dalam keluarga memainkan peran sentral. Simpulan dari penelitian ini memberikan dasar yang kuat untuk pengembangan program pencegahan stunting yang lebih terfokus, memperlihatkan perlunya peningkatan aksesibilitas fasilitas kesehatan, perhatian terhadap kebijakan mendukung kesehatan ibu bekerja, dan pendekatan holistik untuk meningkatkan pola asuh positif.